Skinny meals : everything you need to lose weight-fast! - Harper, Bob (Ballantine Books Trade Paperbacks, 2014)
"From Bob Harper, star of NBC's ongoing smash reality show The Biggest Loser, come 100 delicious new recipes (all of them under 330 calories!), a month of new menu plans, and indispensable shopping lists and cooking tips that all follow Bob's practical strategies for getting thin! In The Skinny Rules, super-motivator Bob Harper introduced the twenty nonnegotiable eating and lifestyle principles that pave the way to quick and permanent weight loss. Since then, thousands of fans asked for more guidance and inspiration! Skinny Meals answers the call, delivering 100 new Skinny Rules-abiding recipes (all of them under 350 calories!) and a month's worth of new menu plans that will satisfy you at every meal. From an Apple Pie Shake for breakfast to Zucchini Noodles with Avocado Cream Sauce for dinner, Bob has done all the tricky calorie, protein, carb, sodium, and fiber counting so you can meet his Rules goals without even thinking about them! With easy, prepare-ahead strategies, handy shopping lists, and cooking tips, Skinny Meals is your ultimate guide to slimming down and staying fit. Just shop, chop, and enjoy!"--